DIGITALIZATION MEETS TRADITION: A FRAMEWORK FOR LOCALIZED MORAL EDUCATION IN PRIMARY SCHOOLS - Fadilah (SMART: Journal of Multidisciplinary Educational, 2025)
This study aims to explore the integration of local wisdom into digital character education frameworks for primary school students. Grounded in the increasing urgency to harmonize global digital pedagogy with indigenous values, the research employs a library research method through a systematic literature review of 28 peer-reviewed journal articles published within the last five years. The analysis identifies effective practices, challenges, and opportunities in blending cultural heritage with digital instruction. Findings reveal that localized moral education—delivered via digital storytelling, culturally relevant gamification, and teacher-facilitated interactive media—fosters deeper value internalization and enhances student engagement. Moreover, the study highlights significant enabling factors, including community involvement, digital teacher competence, and institutional flexibility, while acknowledging barriers such as limited infrastructure and lack of culturally grounded digital resources. The novelty of this study lies in its proposed conceptual framework that bridges traditional character-building narratives with technology-enhanced education, offering a scalable and culturally adaptive solution. By positioning local wisdom not as a counterforce to technology but as a foundation for meaningful moral learning, the research contributes to global discourses on culturally responsive pedagogy. In conclusion, the integration of tradition and digital innovation is not only feasible but essential for fostering ethical and civic-minded students in the 21st century. The resulting framework is expected to be adaptable for diverse educational systems seeking to preserve cultural identity while embracing digital advancement.